Relationship between Candida and nocturnal denture wear: quantitative study - Compagnoni, Marco Antonio [UNESP]; Souza, R. F.; Marra, J.; Pero, Ana Carolina [UNESP] [UNESP]; Barbosa, Débora de Barros [UNESP] (Blackwell Publishing, 2007)
The purpose of this study was to evaluate the relationship between Candida and denture wear during the night. Twenty-four edentulous volunteers were randomly divided into two groups. Group I (GI, n = 11) was composed of volunteers who wore their complete dentures day and night and Group H (GII, n = 13) was composed of volunteers who wore their complete dentures only during the day. Three examination periods were performed for both groups. In GI, the first examination (A) was carried out after overnight denture wearing. Subsequent examinations were conducted after one (B) and seven nights (C) without denture use during sleep. In GII, the first (A) was done without previous use during sleep, and the following were carried out after one (B) and seven nights (C) of overnight denture wearing. Total un-stimulated saliva was collected in a sterile container and cultured in duplicate inside Petri dishes. The values of colony forming units (CFU mL(-1) +/- s.d.) were obtained: GI A - 10.1 x 10(3) +/- 1.2 x 10(4), B - 2.0 x 10(3) +/- 2.6 x 10(3), and C - 2.6 x 10(3) +/- 5.9 x 10(3) and GII: A - 0.4 x 10(3) +/- 0.6 x 10(3), B - 9.4 x 10(3) +/- 17.7 x 10(3) and C - 6.3 x 10(3) +/- 15.3 x 10(3). The mean counts for Candida sp. were expressed as log (CFU + 1) mL(-1) and statistical significance of differences among groups was tested by ANOVA (alpha = 0.05). Multiple comparisons were performed according to Bonferroni test and indicated significant differences between A-B and A-C, but not between B and C for both groups. It was concluded that there is a significant relationship between continuous denture wear and Candida sp.
Keywords: Candida; complete dentures; elderly people; candidiasis; denture wearer